The Cycle of Violence: Abused and Neglected Girls to Adult Female Offenders - Widom, Cathy Spatz; Osborn, Max (Feminist criminology, 2021)
Drawing on findings from a prospective cohort design study that followed abused and neglected children and demographically matched controls into adulthood, this paper focuses on these abused and neglected girls and one important consequence—the extent to which these victims become offenders themselves. We ask four questions: Is criminal behavior among abused and neglected girls and women rare? Are abused and neglected girls at increased risk for becoming violent offenders? Does childhood maltreatment affect criminal career trajectories for girls? Do maltreated girls grow up to maltreat their own children? We conclude with discussion, suggestions for future research, and implications.